Production of Plant Growth Promoting Antagonistic Rhizobacteria to Promote Cucumber Growth and Control Leaf Spot Disease (Corynespora cassiicola) - Nuntavun Riddech (Science Faculty of Chiang Mai University, 2019)
The objective of this study was to assess the potential of two rhizobacteria isolates (A2R1B8 and A2R3B24) as antagonistic bacteria to control leaf spot disease (Corynespora cassiicola) and enhance plant growth of cucumber, as an alternative to using chemicals.. An inhibition test of fungal pathogen C. cassiicola was performed utilizing the dual culture technique. This result showed that the two isolates could inhibit fungal pathogen. The properties of isolates A2R1B8 and A2R3B24 to promote plant growth were also tested. It was found that the two antagonistic rhizobacteria isolates revealed the properties of atmospheric N fixation, solubilization of phosphate and production of IAA (19.8 µML-1 and 23.8 µML-1, respectively). Preparation of antagonistic rhizobacteria as co-microbial inoculums was performed by culturing the isolates on carriers such as soil, manure, bagasses and filter cake. The number of microbial inoculums surviving on carriers was calculated. Results demonstrated that the highest survival number was achieved on filter cake. Testing infection of C. cassiicola leaf spot disease on cucumber showed 62.7% of infection of the leaf spot disease on cucumber leaf. Use of antagonistic rhizobacteria to inhibit C. cassiicola in the pot experiments by spraying showed a percentage reduction of the disease. Identification of antagonistic rhizobacteria isolates utilizing 16S rDNA sequence analysis showed a 99.93% degree of similarity of A2R1B8 with Bacillus amyloliquefaciens subsp. plantarum and of A2R3B24 with Bacillus tequilensis. The results from this research can be applied in agriculture in order to reduce the use of chemicals in crop cultivation.